Systems thinking for health systems strengthening - Organization, World Health (World Health Organization, 2009)
Many developing countries are looking to scale-up what works through major systems strengthening investments. With leadership, conviction and commitment, systems thinking can facilitate and accelerate the strengthening of systems to more effectively deliver interventions to those in need and be better able to improve health in an equitable way. Systems thinking is not a panacea. Its application does not mean that resolving problems and weaknesses will come easily or naturally or without overcoming the inertia of the established way of doing things. But it will identify, with more precision, where some of the true blockages and challenges lie. It will help to: 1) explore these problems from a systems perspective; 2) show potentials of solutions that work across sub-systems; 3) promote dynamic networks of diverse stakeholders; 4) inspire learning; and 5) foster more system-wide planning, evaluation and research. And it will increase the likelihood that health system strengthening investments and interventions will be effective. The more often and more comprehensively the actors and components of the system can talk to each other from within a common framework --communicating, sharing, problem-solving - the better chance any initiative to strengthen health systems has. Real progress will undoubtedly require time, significant change, and momentum to build capacity across the system. However, the change is necessary - and needed now. This report therefore speaks to health system stewards, researchers and funders and maps out a set of strategies and activities to harness these approaches, to link them to these emerging opportunities and to assist systems thinking to become the norm in design and evaluation of interventions in health systems. But, the final message is to the funders of health system strengthening and health systems research who will need to recognize the potential in these opportunities, be prepared to take risks in investing in such innovations, and play an active role in both driving and following this agenda towards more systemic and evidence-informed health development.